2014
DOI: 10.14370/jewnr.2014.20.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Self-Efficacy, Spiritual Well-Being, and Job Stress in Clinical Nurses

Abstract: Purpose: This study was to identify the extent of and the relationships among self-efficacy, spiritual well-being, and job stress in clinical nurses. Methods: The subjects were 201 clinical nurses from three different general hospitals in B city. Data were collected from May 26 to August 9, 2012 and analyzed by using descriptive statistics, independent t-test, One-way ANOVA, Sheffé test, and Partial correlation coefficients. Results: The mean scores of self-efficacy, spiritual well-being, and job stress were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Casali et al ( 2021 ) found a positive relationship between self-efficacy and transcendent character strength. Likewise, the previous research results also support this finding (Adegbola, 2011 ; Asghari et al, 2014 ; Han et al, 2014 ; Jun & Lee, 2016 ; Rakhshanderou et al, 2020 ; Wong & Longshore, 2008 ). Adegbola ( 2011 ) carried out a study to assess the relationship spirituality has with self-efficacy and quality of life in adult patients and found a strongly significant correlation to exist among the variables.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Casali et al ( 2021 ) found a positive relationship between self-efficacy and transcendent character strength. Likewise, the previous research results also support this finding (Adegbola, 2011 ; Asghari et al, 2014 ; Han et al, 2014 ; Jun & Lee, 2016 ; Rakhshanderou et al, 2020 ; Wong & Longshore, 2008 ). Adegbola ( 2011 ) carried out a study to assess the relationship spirituality has with self-efficacy and quality of life in adult patients and found a strongly significant correlation to exist among the variables.…”
Section: Discussionsupporting
confidence: 65%
“…Many studies have found a positive relationship between spirituality and self-efficacy (Adegbola, 2011 ; Asghari et al, 2014 ; Han et al, 2014 ; Jun & Lee, 2016 ; Rakhshanderou et al, 2020 ; Wong & Longshore, 2008 ). Some approaches have shown people’s spirituality development to be about cognitive abilities, behaviors, and skills (Oman et al, 2009 ).…”
Section: Present Studymentioning
confidence: 99%
“…According to the findings, most of the studied nurses were at an average level in terms of spiritual health. In other studies, the level of spiritual health of nurses was reported as average [23][24][25] . In a study that was conducted to investigate the nurses' perceptions of the competence of spiritual care, preparation and barriers to provide spiritual care, and the frequency of providing spiritual care, the participants generally stated that they are competent in providing spiritual care 26 .…”
Section: Discussionmentioning
confidence: 99%